Dynamic mechanical analysis of continuous carbon fiber‐reinforced polyetheretherketones under multi‐consecutive temperature scans. Issue 9 (13th July 2022) - Li, Shiping; Zhang, Yibei; Chen, Wujun; Chen, Longlong; Fang, Guangqiang; Peng, Fujun
Abstract: The study analyzed the dynamics mechanical properties of carbon fiber‐reinforced polyetheretherketone (CF/PEEK) under multi‐consecutive temperature scans and establish an evaluation model of storage modulus to facilitate application in high/low temperature. The dynamic mechanical properties of CF/PEEK laminate sheets obtained via hot‐pressing procedure were subjected to a dynamic mechanical cycle test. The micromorphology and microstructure were observed with a scanning electron microscopy. The structural evolution of CF/PEEK and the interface between carbon fiber and PEEK matrix were analyzed. The characteristic variation of storage modulus, loss modulus, and loss factor are discussed and the damping properties are studied in different temperature ranges. The results show that the dynamic mechanical properties of CF/PEEK were become stabilized after the first temperature scan, while the glass transition temperature remained basically unchanged. The storage modulus of the material increased by 15.8% and the peak value of the loss factor curve increased by 14.4%. Based on the experimental data, an evaluation model of the storage modulus was formulated and validated by the test results obtained to provide an accurately predicting the dynamic mechanical properties of CF/PEEK and expand its engineering applications. Abstract : After the first temperature scan, a certain amount of polyetheretherketone (PEEK) is embedded and attached in the grooves among the fibers, and the distribution of PEEK in the fiber is more uniform. The contact area and bonding strength between the fiber and the matrix increases, and the interface performance is effectively improved, resulting in enhanced dynamic mechanical properties of carbon fiber‐reinforced polyetheretherketone (CF/PEEK). For this reason, the characteristic variation of storage modulus, loss modulus, and loss factor are discussed, and the fitted storage modulus model can accurately reflect the storage variation of CF/PEEK.